FEATURES OF REPARATIVE OSTEOREGENERATION AFTER TEETH EXTRACTION, METHODS OF REPLACEMENT OF BONE TISSUE DEFECT OF THE JAWS (LITERATURE REVIEW) - M.O. Kolesnichenko (Український стоматологічний альманах, 2022)
Introduction. Vertical and horizontal atrophy of the alveolar process, which occurs after tooth extraction, can create negative prerequisites for the surgical stage of dental implantation and requires additional surgical interventions.